Photocatalytic degradation of butyric acid over Cu2O/Bi2WO6 composites for simultaneous production of alkanes and hydrogen gas under UV irradiation. (23rd March 2017) - Zheng, Xian-Jun; Li, Cui-Ling; Zhao, Meng; Zheng, Zhi; Wei, Li-Fang; Chen, Feng-Hua; Li, Xi-Li
Abstract: In present study, photocatalytic production of alkanes and hydrogen gas from butyric acid solution over Cu2 O/Bi2 WO6 composites has been investigated under UV irradiation. The Cu2 O/Bi2 WO6 heterojunction composites were synthesized by a two-step method, first by a hydrothermal method, and then by a simple reduction precipitation method. The as-prepared samples were characterized by X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), ultraviolet–visible diffuse reflection spectroscopy (DRS) and photoluminescence spectroscopy (PL). In Cu2 O/Bi2 WO6 composites, the larger spherical Cu2 O were covered by smaller Bi2 WO6 nanosheets. The 24.36 wt%Cu2 O/Bi2 WO6 composite showed the highest photocatalytic activity for production of alkanes and hydrogen gas. The enhancement in photocatalytic activity can be ascribed to increment in light absorption and effective inhibition of recombination of photogenerated carriers at the heterostructure interface. Based on distributions of gaseous products and intermediates in liquid, a possible mechanism for photocatalytic decomposition of butyric acid over Cu2 O/Bi2 WO6 composites is proposed. Our results provide a method for pollutants removal with simultaneous production of alkanes and hydrogen. Graphical abstract: Highlights: Butyric acid is first used as electron donors during photocatalytic H2 process. First report about coproduction of alkanes and hydrogen by Cu2 O/Bi2 WO6 . A new pathway for photocatalytic production of alkanes and hydrogen from butyric acid. A novel process for coproduction hydrogen and alkane by coupling biological fermentative process with photocatalytic process.